Pathomorphosis of stage IIB cervical cancer in preoperative radiation therapy - A.E. Kryzhanivska; E.O. Kindrativ; I.O. Mykhailiuk (Zaporozhye State Medical University, 2013)
With the purpose of study of medical radiation pathomorphosis morphological research of 53 cases of stage IIB cervical cancer was conducted during the application of preoperative radiation therapy. The degree of expression of medical pathomorphosis of parenchymalstromal components was assessed on the scale of G.A. Lavnikova (1976). The analysis of medical pathomorphosis has shown that I degree lesion was fi xed in 2 cases (3,7%), II - in 20 (37,7%), III - in 11 (20,8%), IV - in 20 (37,7%). The index of damage is 56,7%. High frequency (96,2%) of radiation pathomorphosis development confi rms the radiosensitivity of stage IIB cervical cancer. Application of preoperative radiation therapy determines the devitalisation of tumour parenchyma mainly in superfi cial areas and has the focal character. Development of pathomorphosis does not depend on the form of tumour growth, but histological variant of squamous cell carcinoma, namely non-keratinizing (77,4%) can be an indication for preoperative radiation therapy. The obtained results of radiation pathomorphosis assessment allow planning the subsequent tactics of management of patients with the application of additional methods of treatment.